Eruptive Tumors of the Follicular Infundibulum: An Unexpected Diagnosis of Hypopigmented Macules - Poonkiat Suchonwanit (2018)
© 2015, The Author(s). Background: Tumor of the follicular infundibulum (TFI) is considered as a rare benign neoplasm providing two distinctive clinical patterns: the solitary and the eruptive form. The clinical presentations resemble many other dermatologic conditions and require histopathological study to make a definite diagnosis. Objective: To inform physicians of a clinical presentation of TFI. Case Report: We report on a 50-year-old man who presented with multiple asymptomatic hypopigmented macules resistant to the treatments. The histopathological study was consistent with tumors of the follicular infundibulum. Conclusion: Hypopigmented macules are one of the more common clinical presentations in dermatological practices. It is important to include TFI in the differential diagnosis when a patient with hypopigmented lesions does not respond to the treatment based on the clinical diagnosis.